Cost competitiveness of Chinese and Finnish fabricated metal industries - Enjing Li; Paavo Suni; Yanyun Zhao (The Research Institute of the Finnish Economy (ETLA), 2008)
This study focuses on the labour cost competitiveness of fabricated metal industry in China and Finland in particular, using the corresponding German, the US and Estonian industries as a point of comparison in the early 2000s. This study deepens the analysis of the earlier study of the cost competitiveness of the manufacturing industries in the same group of countries. Separate studies focusing on the labour cost competitiveness are carried out in a parallel manner on the paper and pulp and metal industries. The results of these three sector studies deepen the knowledge about the change of competitiveness and its level. Large unit labour cost differences in a common currency were obviously a key factor behind exceptionally rapidly changing international production and trade structures in the late 1990s and early 2000s. The Chinese fabricated metal industry grew by about 22 per cent per year in 2000-2007 as the average annual growth of the value added of world manufacturing volume was only 3 per cent in 2000-2006. Nominal wages as such do not imply good international competitiveness. Chinese wages are, however, low even if their low labour productivity is taken into account and costs per unit of production are compared in a common currency. The relative levels of the Chinese unit labour costs vis-à-vis Germany, using the unit value ratios (UVR) to make the production volumes comparable, were estimated to be about 2 per cent in the fabricated metal industry. The ratio has even declined in early 2000s and has stayed relatively stable after that till 2007. Improving labour productivity in China had compensated for the effects of rapidly rising wages and an appreciating Renminbi. The outlook of the fabricated metal industry is clouded by the difficult global financial crisis, which strongly restricts export possibilities and dampens also the domestic markets of industry. On the other hand the stimulus packages of the government target especially the key demand sectors of the fabricated metal industry.
Keywords: 330; competitiveness; unit value ratio; UVR; fabricated metal industry; NACE 28; Metallindustrie; Arbeitsproduktivität; Arbeitskosten; Internationaler Wettbewerb; China; Finnland